Greenyards'tabir silah - Hunter, Mollie, 1922- (İstanbul, Set -Systems, 2004)
The enclosure movement brought many Scots to exile in America in the middle of the nineteenth century. A fifteen-year-old boy describes the brutality that accompanied the usurpation of small farms of Northern Scotland for sheep grazing and his own role that led to crime and flight to the New World.
Turkish.
Keywords: Adventure and adventurers -- Fiction; Scotland -- Fiction